2017
DOI: 10.18320/jimd/201704.0106
|View full text |Cite
|
Sign up to set email alerts
|

2. Prevalence of Extended spectrum beta- lactamase (ESBL) producing Klebsiella species and Escherichia coli among clinical isolates in a tertiary care hospital

Abstract: Abstract:Background: Klebsiella species and Escherichia coli are members of the family Enterobacteriaceae encountered frequently as opportunistic pathogens in clinical settings. Cephalosporins are considered as first line drugs against Klebsiella species and Escherichia coli. Inappropriate use of β-lactams against gram negative bacteria has resulted in the widespread development of drug resistance. This study was done to know the prevalence of ESBL producing Klebsiella species and Escherichia coli among clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…Antimicrobial susceptibility testing of Klebsiella exhibited 100% resistance to Ampicillin. A previous study showed a similar resistance towards ampicillin (100%) that depicts Klebsiella species are intrinsically resistant to Ampicillin [12].…”
Section: Resultsmentioning
confidence: 60%
“…Antimicrobial susceptibility testing of Klebsiella exhibited 100% resistance to Ampicillin. A previous study showed a similar resistance towards ampicillin (100%) that depicts Klebsiella species are intrinsically resistant to Ampicillin [12].…”
Section: Resultsmentioning
confidence: 60%
“…Creating awareness on antibiotic resistance of organisms, designing and effective implementation of antibiotic policy are few steps to be taken towards handling resistant organisms (ESBL, MBL and AmpC producers) 22,23 . Regular microbiological surveillance is essential to know the prevalence of the these enzymes and their susceptibility pattern.…”
Section: Discussionmentioning
confidence: 99%